2009
DOI: 10.5551/jat.no703
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum 7-Ketocholesterol Concentrations in the Progression of Coronary Atherosclerosis

Abstract: Aim: 7-Ketocholesterol concentrations can be measured in a blood sample; however, the relationship between blood 7-ketocholesterol concentrations and atherosclerotic disease is not well-known. The aim of this study was to clarify the clinical significance of serum 7-ketocholesterol concentrations (s-7KCHO) in the progression of coronary atherosclerosis. Methods: One hundred and thirty-nine subjects with coronary artery disease (CAD, subjects with stable angina pectoris or acute myocardial infarction) and 43 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 54 publications
0
14
0
Order By: Relevance
“…Niemann-Pick type C (NP-C) disease is a rare, autosomalrecessive disorder resulting from homozygous or compound heterozygous NPC1 mutations and is clinically characterized by progressive neurological deterioration and liver/spleen enlargement due to abnormal sequestration of unesterified cholesterol and glycosphingolipids within the late endosome/lysosome compartments (18). Although the biological parents of NP-C patients carrying one mutant NPC1 allele are considered to be physiologically normal, we and others have recently shown that these apparently healthy carriers of heterozygous NPC1 mutation (NPC1 +/2 ) have increased plasma bile acid A (a glycine-conjugated 3b,5a,6b-trihydroxycholanic acid) (19) and 7-ketocholesterol (20), an oxidized lipid involved in atherosclerosis progression (21,22), indicating the potential detrimental effects of heterozygous NPC1 mutation on cardiometabolic functions. To date, no studies have directly and systematically investigated NPC1 mutations and their functional consequences in the pathogenesis of human obesity in the available literature.…”
mentioning
confidence: 99%
“…Niemann-Pick type C (NP-C) disease is a rare, autosomalrecessive disorder resulting from homozygous or compound heterozygous NPC1 mutations and is clinically characterized by progressive neurological deterioration and liver/spleen enlargement due to abnormal sequestration of unesterified cholesterol and glycosphingolipids within the late endosome/lysosome compartments (18). Although the biological parents of NP-C patients carrying one mutant NPC1 allele are considered to be physiologically normal, we and others have recently shown that these apparently healthy carriers of heterozygous NPC1 mutation (NPC1 +/2 ) have increased plasma bile acid A (a glycine-conjugated 3b,5a,6b-trihydroxycholanic acid) (19) and 7-ketocholesterol (20), an oxidized lipid involved in atherosclerosis progression (21,22), indicating the potential detrimental effects of heterozygous NPC1 mutation on cardiometabolic functions. To date, no studies have directly and systematically investigated NPC1 mutations and their functional consequences in the pathogenesis of human obesity in the available literature.…”
mentioning
confidence: 99%
“…Concentrations of 7-ketocholesterol up to 10 M are found in macrophage-derived foam cells of atherosclerotic plaques and in cataract lenses, probably as a result of excessive autooxidation [133][134][135][136]. Importantly, in patients with coronary artery disease, significantly elevated serum 7-ketocholesterol levels compared with control subjects (19 ng/ml versus 32 ng/ml (48 nM versus 80 nM)) were observed [137]. Serum 7-ketocholesterol levels strongly correlated with the presence of acute myocardial infarction, the number of affected blood vessels and high sensitive C-reactive protein concentrations, suggesting a close association between elevated serum 7-ketocholesterol and the progression of coronary atherosclerosis and inflammation.…”
Section: Role Of 11␤-hsd1 In the Metabolism Of 7-ketocholesterolmentioning
confidence: 99%
“…Exercise stress test (effort test) is a noninvasive test, this provides a great advantage, but it is necessary to increase the accuracy of the test because the specificity of the test is low and its evaluation is subjective (4, 5). Oxysterols have been implicated in the formation and progression of atherosclerotic plaques (6, 7). 7-ketocholesterol (7-KC), 7ß-hydroxycholesterol (7ß-OHC), beta-isomers of epoxide, 27-hydroxycholesterol (27-OHC) and cholestane-3β,5α,6β-triol (C-triol) have been shown to increase in plasma and/or atherosclerotic plaque in various studies (8, 9, 10, 11, 12).…”
Section: Introductionmentioning
confidence: 99%